A Conversation with Phevos Simeonidis (Disinfaux Collective), 21 July 2021. Issue 1 (1st June 2022) - Boursinou, Maria Nerina; Monforte, Pierre; Simeonidis, Phevos
Abstract: In this interview with Nerina Boursinou and Pierre Monforte, Phevos Simeonidis—cofounder of the Disinfaux Collective—reflects on the role of civil society organizations in the field of refugee support in Greece, in particular through the focus on their relations with public authorities. The interview provides an account of the changing environment in the field of migration and the diversity of the organizations working to support refugees in Greece, while it highlights such organizations' ambivalent relations with public authorities. Moreover, the interview discusses the impact of the measures taken by the Greek government(s) to control or repress the activities of civil society organizations in recent years, including their criminalization. Finally, it makes reference to the complex ethics that accompany migration research and support practices, especially in relation to the collective's operation and decision-making processes.